The Efficacy of Providing Education Regarding the First 1000 Days of Life on the Knowledge of Pregnant Women at the Tombulilato Community Health Center - Hasmawati Hasmawati; Anik Purwati (International Forum of Researchers and Lecturers, 2025)
Stunting, also known as growth failure in children, is a condition caused by a child's nutritional needs not being met for a long time, specifically during the first 1,000 days of life. The first 1,000 days of life are the first 270 days (nine months) in the mother's womb plus the first 730 days (two years) of a baby's life after birth. Education is a learning process aimed at developing the potential or quality of thought patterns and knowledge of an individual or group. One of the goals of education is to increase public knowledge. The target group for the first 1,000 days of life is pregnant women. The purpose of this study was to determine the effect of education on pregnant women's knowledge about the first 1,000 days of life at the Tombulilato Community Health Center, Bone Raya District, Gorontalo City. The type of research used is Quasi Experiment with a two group pretest and posttest design approach. The sample in this study were 32 pregnant women in the intervention group and 32 in the control group. Data collection was done through a questionnaire. Data were analyzed using a paired T test with a 95% confidence interval (CI) and α <0.05. The results of the study showed that Educational Intervention had a significant effect on the knowledge of pregnant women (p = 0.000) in the First 1000 Days of Life in the Tombulilato Health Center area, Bone Raya District. It is hoped that more practical information will be provided to the community, especially prospective mothers, in preparing a quality next generation, especially in the First 1000 Days of Life. As well as optimizing Posyandu services, and involving the participation of families such as husbands and parents when socialization and information provision are carried out.